Comparative Economic Analysis and Traffic Potential of Coastal Shipping in India - Planning Commission (Planning Commission, 1981)
Coastal shipping in India has emerged as a cost-effective and energy-efficient alternative to road and rail transport, particularly for bulk commodities. Despite the country’s extensive coastline and port facilities, coastal shipping traffic has stagnated due to competition from surface transport and operational inefficiencies. This study examines the coastal hinterlands, current traffic trends, and competitive costs, highlighting commodities like coal, salt, cement, and fertilizers as having substantial future potential. Policy interventions such as cargo reservation, port development, customs reforms, and tonnage augmentation are essential to revitalize the sector. Insights from India’s experience underscore the role of coordinated infrastructure and strategic planning in enhancing coastal trade, offering valuable lessons for emerging economies seeking sustainable transport solutions.
Government of India Planning Commission UNDP Transport Policy Planning Project May 1981
Government of India Planning Commission UNDP Transport Policy Planning Project
Keywords: Coastal Shipping; India; Freight Transport; Bulk Commodities; Port Infrastructure; Traffic Potential; Transport Costs; Policy Recommendations; Hinterland Economy; Rail Competition; Energy Efficiency; Maritime Trade